Pengaruh Kebijakan Kepada Desa terhadap Pengembangan UMKM di Desa Hulawa Kecamatan Telaga Kabupaten Gorontalo - Nur Mutiya K. Tamu; Roy Hasiru; Cristian Polamolo; Melizubaida Mahmud; Rierind Koniyo (Transbahasa, 2026)
This study aims to analyze the effect of village head policies on the development of Micro, Small, and Medium Enterprises (MSMEs) in Hulawa Village, Telaga District, Gorontalo Regency. MSMEs play a strategic role in enhancing the rural economy; therefore, support from village government policies is a crucial factor in promoting business growth and sustainability. This research employed a quantitative approach using simple linear regression analysis. The population of this study also served as the sample, consisting of 49 MSME actors in Hulawa Village. Data were collected through questionnaires developed based on indicators of village head policies and MSME development. The data were analyzed using t-tests and the coefficient of determination (R²). The results indicate that village head policies have a significant effect on MSME development, as evidenced by a significance value of 0.016 (<0.05). The coefficient of determination of 11.8% shows that village head policies contribute 11.8% to MSME development, while the remaining 88.2% is influenced by other factors beyond the scope of this study. It can be concluded that village head policies play a role in encouraging MSME development; however, additional supporting factors are needed to achieve more optimal outcomes.